Protective effects of chronic melatonin treatment against renal injury in streptozotocin-induced diabetic rats - (:unkn) unknown (BLACKWELL MUNKSGAARD, 2003)
The aim of this study was to investigate the effects of melatonin as an antioxidant, on prevention and treatment of streptozotocin (STZ)induced diabetic renal injury in rats. Male Wistar rats were divided into four groups: ( 1) untreated, ( 2) melatonin-treated, ( 3) untreated diabetic (UD), ( 4) melatonin-treated diabetic ( MD). Experimental diabetes was induced by single dose ( 60 mg/kg, i.p.) STZ injection. For 3 days prior to administration of STZ, melatonin was injected ( 200 mug/kg/day, i.p.); these injections were continued until the end of the study ( 4 weeks). Malondialdehyde (MDA) levels as a marker of lipid peroxidation were significantly increased in the renal homogenates of UD animals and decreased after melatonin administration. The activity of the antioxidative enzyme glutathione peroxidase (GSH-Px) was significantly reduced in UD rats. Melatonin treatment reversed STZ-induced reduction of GSH-Px activity without having an effect on blood glucose. Upon histopathological examination, it was observed that the melatonin treatment prevented the renal morphological damage caused by diabetes. Upon immunohistochemical investigation, glomerular anti-laminin beta1 staining decreased in MD rats. Additionally, no tubular anti-IGF-1 staining was observed in melatonin-treated rats. In conclusion, chronically administered melatonin reduced renal injury in STZ-induced diabetic rats and thus it may provide a useful therapeutic option in humans to reduce oxidative stress and the associated renal injury in patients with diabetes mellitus.
Keywords: diabetic renal injury; glutathione peroxidase; immunohistochemistry; malondialdehyde; melatonin; oxidative stress; streptozotocin; INCREASED COLLAGEN PRODUCTION; INDUCED LIPID-PEROXIDATION; MESANGIAL CELLS; OXIDATIVE STRESS; EXTRACELLULAR-MATRIX; HIGH GLUCOSE; REACTIVE OXYGEN; KIDNEY-DISEASE; VITAMIN-E; MELLITUS